Wanita & keadilan (Kuala Lumpur ANZ Charisma, 1999)
Women's rights and women according to Malaysian laws; collection of papers.
Includes bibliographical references (p. 177-188).
Keywords: Women's rights -- Malaysia; Women -- Legal status, laws, etc. -- Malaysia